Role of Vitamin D in the Hygiene Hypothesis: The Interplay between Vitamin D, Vitamin D Receptors, Gut Microbiota, and Immune Response - Clark, Allison; Mach, Núria (Frontiers in Immunology, 2016)
The hygiene hypothesis postulates that higher levels of cleanliness and improper exposure to microorganisms early in childhood could disturb the intestinal microbiome resulting in abnormal immune responses. Recently, more attention has been put on how a lack of sun exposure and consequently vitamin D deficiency could lead to less immune tolerance and aberrant immune responses. Moreover, vitamin D receptor (VDR) function has been positioned to be a critical aspect of immune response and gut homeostasis. Therefore, this review focuses on the role that the interaction between vitamin D, VDR function and gut microbiome might have on autoimmune diseases in the context of the hygiene hypothesis. Literature shows that there is a high correlation between vitamin D deficiency, VDR dysfunction, gut microbiota composition and autoimmune diseases. The biologically active form of vitamin D, 1,25(OH)2D3, serves as the primary ligand for VDRs which have been shown to play a fundamental role in reducing autoimmune disease symptoms. Although the biological functions of VDR, the effects of its genetic variants and the effects of epigenetic profiles in its promoter region are largely unknown in humans, studies in murine models are increasingly demonstrating that VDRs play a crucial role in attenuating autoimmune disease symptoms by regulating autophagy and the production of antimicrobial peptides such cathelicidin and β-defensin, which are responsible for modifying the intestinal microbiota to a healthier composition. Remarkably, evidence shows that hormonal compounds and byproducts of the microbiota such as bile acids might also activate VDR. Therefore, understanding the interaction between VDR and gut microbiota is of the utmost importance towards understanding the rise in autoimmune diseases in Western countries. We have gained insights on how the VDR functions affects inflammation, autophagy, and microbiota composition that could lead to the development of pathogenesis of autoimmune diseases, while confirming the role vitamin D and VDRs have in the context of hygiene hypothesis.